“Motoso y terruco”: Language Ideologies and Racialization in Peruvian Politics - Zavala, Virginia (2022)
In this article, we analyze uses of “motoso” and “motoso terruco” in Peruvian politics, produced in social networks (Twitter and Facebook), which account for a semiotic process of indexical inversion in the functioning of the language ideology of motoseo. In this context, speaking “motoso” no longer refers to concrete forms of speech associated with a social group, but to practices and discourses that produce a meta-pragmatic knowledge of how “Indians” supposedly speak or should speak. The reinvention of “motoso” in articulation with “terruco” would be revealing new dynamics in the way cultural racism functions in Peru. Specifically, it emerges as a strategy to racialize, relocate and, above all, silence political figures who are seen as potential threats to a prevailing social order of colonial and neoliberal character.